The Tradition of Islamic Scholarship and Thought in Indonesia and Brunei Darussalam - Afandi, Richad Dedi Syahbudin (Proceedings: International Seminar On Educational Studies, 2025)
This article discusses the scientific traditions and Islamic thought in Indonesia and Brunei Darussalam in the context of history, culture, and their influence on the development of Islamic civilization in the archipelago. This study uses a qualitative approach through library research, utilizing various scientific literature, both classical and contemporary. The results of the study show that both Indonesia and Brunei Darussalam have strong Islamic roots based on the values of Ahlussunnah wal Jama'ah. In Indonesia, Islamic boarding schools have become centers of Islamic education that play an important role in maintaining the continuity of knowledge and morals in society. Meanwhile, in Brunei Darussalam, Islamic scholarship has developed under the protection of the royal system, which places Islam as the basis of the state ideology. The tradition of Islamic scholarship in both countries also reflects efforts to balance traditional values and modernity. Through this integration, both countries contribute to strengthening a moderate, inclusive Islamic identity that is oriented towards the advancement of civilization